(Un)desired racial aesthetics in the provocative elements of the Celpe-Bras oral test? : Racialized perceptions about the exclusion of the black segment and overvaluation of whiteness - Moraes, Robson Batista; Melo, Amanda Santiago Souza; Santana, Erivelton Nonato de (The ESPecialist, 2024)
Whiteness has a kind of non-verbalized contract, in other words, a narcissistic pact whose main purpose is to maintain the economic and symbolic privileges of white people and to exclude black people. This research is in the field of Applied Linguistics, inside the large field within Language and in the subarea of Portuguese Studies for Speakers of Other Languages. In fact, this research aims to analyse racism and language taking the Provoking Elements (PEs) used in the oral test of Celpe-Bras (Certificate of Proficiency in Portuguese for Foreigners) focusing on 20 PEs from the edition of the first semester of 2005.